2003
DOI: 10.1124/jpet.102.042226
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization ofN,N-Dimethyl-2-(2-amino-4-methylphenyl thio)benzylamine as a Ligand of the Serotonin Transporter with High Affinity and Selectivity

Abstract: Serotonin transporter has a key-role in regulation of serotoninergic function, and is involved in numerous neurodegenerative and psychiatric disorders. To obtain an efficient radioactive ligand allowing the study of this transporter in vitro and in vivo, we synthesized a new diphenyl sulfide derivative, N,N-dimethyl-2-(2-amino-4-methylphenylthio)benzylamine or MADAM. We present here extensive pharmacological characterization of this compound.[3 H]MADAM bound to serotonin transporters with a very high affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 35 publications
7
16
0
Order By: Relevance
“…[ 3 H]MADAM, [ 123 I]ADAM, and [ 11 C]DASB did not display species differences in receptor affinity. The K d values obtained (0.11, 0.05, and 0.34 nM, respectively) were in accordance with previously published results reporting K d values in the rat brain of 0.06, 0.15, and 0.54 nM at 228C, respectively (Chalon et al, 2003;Choi et al, 2000;Lundquist et al, 2005). The K d (0.25 nM) and B max (105 fmol/mg protein) values obtained with [ 11 C]DASB in the monkey cortex are concordant with another study, where a K d value of 0.20 nM and a B max value of 66 fmol/mg protein have been obtained with [ 3 H]DASB binding in tissue homogenates of rhesus monkey frontal cortex (Zeng et al, 2006 I]ADAM contra 100-170 fmol/ mg protein with the other radioligands).…”
Section: Species Differencessupporting
confidence: 92%
“…[ 3 H]MADAM, [ 123 I]ADAM, and [ 11 C]DASB did not display species differences in receptor affinity. The K d values obtained (0.11, 0.05, and 0.34 nM, respectively) were in accordance with previously published results reporting K d values in the rat brain of 0.06, 0.15, and 0.54 nM at 228C, respectively (Chalon et al, 2003;Choi et al, 2000;Lundquist et al, 2005). The K d (0.25 nM) and B max (105 fmol/mg protein) values obtained with [ 11 C]DASB in the monkey cortex are concordant with another study, where a K d value of 0.20 nM and a B max value of 66 fmol/mg protein have been obtained with [ 3 H]DASB binding in tissue homogenates of rhesus monkey frontal cortex (Zeng et al, 2006 I]ADAM contra 100-170 fmol/ mg protein with the other radioligands).…”
Section: Species Differencessupporting
confidence: 92%
“…After demonstrating promising characteristics in nonhuman primate PET studies, [ 11 C]MADAM ( N,N ‐dimethyl‐2‐(2‐amino‐4‐methylphenylthio)benzylamine) was tested in humans . The brain accumulation pattern was consistent with human postmortem SERT binding with [ 3 H]MADAM as well as [ 3 H]imipramine, [ 3 H]paroxetine, and [ 3 H]citalopram . In a test–retest study, [ 11 C]MADAM had excellent reproducibility when done several weeks apart .…”
Section: Current Radioligands For Imaging the 5‐ht Systemsupporting
confidence: 70%
“…This explanation is however unlikely as in vitro binding studies using rat cortex homogenate at 22°C have demonstrated that citalopram and other SSRIs inhibit all specific binding of [ 3 H]MADAM and that the inhibition is best described by a one-site binding model (Chalon et al 2003 (Quelch et al 2012). It can thus not be ruled out that incomplete inhibition of [ 11 C]MADAM by escitalopram and citalopram may partly be due to a cellular redistribution of SERT which affects escitalopram and citalopram binding differently than [ 11 C]MADAM binding.…”
Section: Discussionmentioning
confidence: 92%